Reach for the Summit - M-S3-A2

Algebra Level 4

A sequence { a n } \{a_n\} is such that a 1 = 1 a_1=1 , a 2 = 3 a_2=3 , a 3 = 6 a_3=6 , and a n = 3 a n 1 a n 2 2 a n 3 \ a_n=3a_{n-1}-a_{n-2}-2a_{n-3} for n 4 n \ge 4 .

If a n > λ × 2 n 2 a_n>\lambda \times 2^{n-2} for all n 4 n \ge 4 , find the maximum integer value of λ \lambda .


Reach for the Summit problem set - Mathematics


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Jul 23, 2020

From the linear recurrence relation a n = 3 a n 1 a n 2 2 a n 3 a_n = 3a_{n-1} - a_{n-2} - 2a_{n-3} , the characteristic polynomial is as below:

r 3 3 r 2 + r + 2 = 0 ( r 2 ) ( r 2 r 1 ) = 0 ( r 2 ) ( r φ ) ( r + φ 1 ) = 0 where φ = 1 + 5 2 is the golden ratio. \begin{aligned} r^3 - 3r^2 + r + 2 & = 0 \\ (r-2)(r^2 - r -1) & = 0 \\ (r-2)(r-\varphi) \left(r + \varphi^{-1} \right) & = 0 & \small \blue{\text{where }\varphi = \frac {1+\sqrt 5}2 \text{ is the golden ratio.}} \end{aligned}

Therefore a n = c 1 2 n + c 2 φ n + c 3 ( φ 1 ) n a_n = c_1 2^n + c_2 \varphi^n + c_3 (-\varphi^{-1})^n , where c 1 c_1 , c 2 c_2 , and c 3 c_3 are constants. Solving the simultaneous equations below:

{ a 1 = 2 c 1 + c 2 φ c 3 φ 1 = 1 a 2 = 4 c 1 + c 2 φ 2 + c 3 φ 2 = 3 a 3 = 8 c 1 + c 2 φ 3 + c 3 φ 3 = 6 \begin{cases} a_1 = 2c_1 + c_2 \varphi - c_3 \varphi^{-1} = 1 \\ a_2 = 4c_1 + c_2 \varphi^2 + c_3 \varphi^{-2} = 3 \\ a_3 = 8c_1 + c_2 \varphi^3 + c_3 \varphi^{-3} = 6 \end{cases}

we get c 1 = 1 c_1 = 1 , c 2 = 1 5 c_2 = - \dfrac 1{\sqrt 5} , and c 3 = 1 5 c_3 = \dfrac 1{\sqrt 5} . Therefore a n = 2 n φ n ( φ ) n 5 = 2 n F n a_n = 2^n - \dfrac {\varphi^n - (-\varphi)^{-n}}{\sqrt 5} = 2^n - F_n , where F n F_n denotes that n n th Fibonacci number .

Then we have a n > λ × 2 n 2 a_n > \lambda \times 2^{n-2} and λ < a n 2 n 2 = 2 n F n 2 n 2 = 4 F n 2 n 2 < 4 \lambda < \dfrac {a_n}{2^{n-2}} = \dfrac {2^n - F_n}{2^{n-2}} = 4 - \dfrac {F_n}{2^{n-2}} < 4 . Since F n < 2 n 2 F_n < 2^{n-2} for all n 4 n \ge 4 , the right-hand side approaches the maximum of 4 4 , as n n \to \infty . Therefor the maximum integer value of λ \lambda is 3 \boxed 3 .

a 4 = 3 ( 6 ) ( 3 ) 2 ( 1 ) = 13 a_4 = 3(6) - (3) - 2(1) = 13

And 13 > λ × 2 4 2 13 > \lambda × 2^{4-2} so λ < 3.25 \lambda < 3.25 .

Since λ \lambda is constant for all a n > λ × 2 n 2 a_n > \lambda × 2^{n-2} , the floor value of λ \lambda will be the maximum (constant/non increasing afterwards) at a 4 a_4 , which is 3 \boxed{3} .

Qweros Bistoros
Jul 25, 2020

Let x n = a n / 2 n 2 x_{n}=a_{n} / 2^{n-2} our goal to find greatest integer lesser or equal then minimum of this sequence for n 4 n\ge4

x 1 = 2 , x 2 = 3 , x 3 = 3 , x_1=2, x_2=3, x_3=3, and x n = 1 4 ( 6 x n 1 x n 2 x n 3 ) x_n = \frac{1}{4}(6x_{n-1}-x_{n-2}-x_{n-3})

x n x_n is increasing sequence.

It can be proven by induction:

base x 1 x 2 x 3 x_1 \le x_2 \le x_3 is given.

If x n 1 x n 2 x n 3 x_{n-1} \ge x_{n-2} \ge x_{n-3} then x n = 1 4 ( 6 x n 1 x n 2 x n 3 ) 1 4 ( 6 x n 1 x n 1 x n 1 ) = x n 1 x_n = \frac{1}{4}(6x_{n-1}-x_{n-2}-x_{n-3}) \ge \frac{1}{4}(6x_{n-1}-x_{n-1}-x_{n-1}) = x_{n-1}

So minimum of x n x_n for n 4 n \ge 4 is x 4 = 13 4 x_4 = \frac{13}{4} and answer is 13 4 = 3 \lfloor \frac{13}{4} \rfloor = 3

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...